In vitro activity of roxithromycin against the Mycobacterium tuberculosis complex. - Rastogi, N (1995)
Roxithromycin has recently been shown to possess significant in vitro activity against a variety of atypical mycobacteria such as the M. avium complex, M. scrofulaceum, M. szulgai, M. malmoense, M. xenopi, M. marinum, and M. kansasii and rare pathogens like M. chelonei and M. fortuitum. In the present investigation, screening of its in vitro activity was further extended by testing it against 34 strains belonging to the M. tuberculosis complex (including M. tuberculosis, M. africanum, M. bovis, and M. bovis BCG). The MICs were determined by the radiometric BACTEC 460-TB methodology at pHs of both 6.8 and 7.4, as well as with 7H10 agar medium by the 1% proportion method. With the exception of M. bovis BCG (MIC ranges, 0.5 to 4 micrograms/ml at pH 6.8 and 0.25 to 2 micrograms/ml at pH 7.4), MICs for all of the isolates were significantly greater (MIC ranges, 32 to > 64 micrograms/ml at pH 6.8 and 16 to > 32 micrograms/ml at pH 7.4) than those reported previously for atypical mycobacteria. Roxithromycin MICs of 64 or > 64 micrograms/ml for all of the M. tuberculosis isolates screened were found by the 7H10 agar medium method. Roxithromycin, however, showed a pH-dependent bactericidal effect against M. tuberculosis because the drug was relatively more active when it was used at pH 7.4 than when it was used at pH 6.8. We conclude that roxithromycin per se is not a drug of choice for the treatment of M. tuberculosis infection or disease; however, considering its pharmacokinetics, eventual anti-tubercle bacillus activity in an in vivo system cannot yet be excluded. We suggest that the use of roxithromycin in chemoprophylactic regimens for the prevention of opportunistic infections (including M. avium complex infections) in patients with AIDS should be carefully monitored, and patients should be enrolled in such a regimen only after it has been excluded that the patient das an underlying infection of disease caused by M. tuberculosis.